2000
DOI: 10.1016/s0886-3350(00)00479-x
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal neovascularization in myopic eyes after photorefractive keratectomy

Abstract: The incidence of CNV after PRK for myopia was low. Choroidal neovascularization is a possible complication in myopic eyes, and the risk exists before PRK. After PRK, the risk of CNV in myopic patients did not increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…CNV developed in one eye after correction of −12.00 D of myopia 26 months after PRK. They used laser photocoagulation for treatment of CNV 2 . In another study, the same researchers reported one case of CNV after the same number of PRK surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNV developed in one eye after correction of −12.00 D of myopia 26 months after PRK. They used laser photocoagulation for treatment of CNV 2 . In another study, the same researchers reported one case of CNV after the same number of PRK surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Although Loewenstein et al described macular hemorrhage in three patients with high myopia (−13.00 to −20 D) after PRK, 6 to date, there has only been one report of CNV after PRK 2 . Ruiz-Mareno and colleagues evaluated the incidence of CNV in 5963 eyes undergoing PRK for the correction of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Very few cases of CNV formation have been reported after LASIK in a low myope or after hyperopic LASIK. [56][57][58] In the aforementioned series of 5936 eyes treated with PRK published by Ruiz-Moreno et al, 21 there was a single case of extrafoveal CNV (0.02%) which occurred 26 months after treatment. Brancato et al 20 published a series of 1165 myopic eyes with PRK with 3 cases of CNV reported afterward.…”
Section: Cnv Macular Hemorrhage and Lacquer Cracksmentioning
confidence: 97%
“…It may, then, be that detachments observed after laser refractive surgery are no more than would have occurred in any case. Nevertheless, it has been speculated that the rise in IOP and retinal and vitreous stresses involved in applying and releasing the suction ring which is used to stabilise the cornea and obtain a LASIK flap of optimal thickness, together with possible shock waves associated with the laser ablation, may have adverse effects on the posterior eye in the form of detachments, choroidal neovascularisation, macular haemorrhages and macular holes, and optic neuropathy (Charteris et al ., 1997; Ruiz‐Moreno et al ., 1999, 2000a, b; Ellies et al ., 2000; Lee et al ., 2000b; Arevalo et al ., 2001; Cameron et al ., 2001; Chan and Lawrence, 2001). However, Krueger et al .…”
Section: Retina and Vitreous Pathology After Refractive Surgerymentioning
confidence: 99%